An EAGRCH estimation for arbitrage modelling: Pre- and post- crisis - Nayman, Merve (İstanbul Bilgi Üniversitesi, 2015)
[Abstract Not Available]
Arbitraj modelinin EAGRCH ile tahmini: Kriz öncesi ve sonrası